Improving the technological support of dairy cattle breeding - Kondratieva Olga (EDP Sciences, 2021)
The paper discusses the issues of providing the population of the Russian Federation with milk and dairy products, increasing milk production, and implementing investment projects in the industry. It is noted that the technological and technical support, as well as improving the systems of keeping, feeding and milking animals play an important role in solving problems of increasing the efficiency of dairy farming. Particular attention is paid to the introduction of innovative technologies and modern machinery at dairy farms and facilities, including equipment fitted with digital systems for collecting information about the state of animals, milk yield, milking parameters and other indicators, as well as robots. Milking installations provided by the system of machines are designed for milking cows in stalls, milking parlors, as well as in maternity wards. According to their engineering level, they must ensure the fulfillment of the physiological milk let-down requirements, the productive longevity of animals, etc. The developed artificial intelligence system allows planning the efficiency of feeding and monitoring the main processes at a dairy farm. Feed is of paramount importance in the prime cost of raw milk. The cost of feed affects the profitability of production. Spectrometers, including pocket ones, can be used for feed analysis. Improvement of technologies in dairy production will help to increase the competitiveness of the industry.